2016
DOI: 10.1371/journal.pone.0154390
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Triggers Body-Wide Skipping of Multiple Exons of the Spinal Muscular Atrophy Gene

Abstract: Humans carry two nearly identical copies of Survival Motor Neuron gene: SMN1 and SMN2. Loss of SMN1 leads to spinal muscular atrophy (SMA), the most frequent genetic cause of infant mortality. While SMN2 cannot compensate for the loss of SMN1 due to predominant skipping of exon 7, correction of SMN2 exon 7 splicing holds the promise of a cure for SMA. Previously, we used cell-based models coupled with a multi-exon-skipping detection assay (MESDA) to demonstrate the vulnerability of SMN2 exons to aberrant splic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 85 publications
(102 reference statements)
0
38
0
1
Order By: Relevance
“…SMN2 exons 5 and 7 become highly susceptible to skipping under the conditions of oxidative stress, although skipping of SMN1 exon 5 is also enhanced by oxidative stress. A recent study examined the effect of paraquat, an oxidative-stress-causing agent, on splicing of various SMN2 exons in different tissues of a transgenic mouse model harboring SMN2 [120]. Findings of this study revealed tissue-specific effect of oxidative stress on splicing of various SMN2 exons.…”
Section: Alternative Splicing Of Other Smn Exonsmentioning
confidence: 94%
“…SMN2 exons 5 and 7 become highly susceptible to skipping under the conditions of oxidative stress, although skipping of SMN1 exon 5 is also enhanced by oxidative stress. A recent study examined the effect of paraquat, an oxidative-stress-causing agent, on splicing of various SMN2 exons in different tissues of a transgenic mouse model harboring SMN2 [120]. Findings of this study revealed tissue-specific effect of oxidative stress on splicing of various SMN2 exons.…”
Section: Alternative Splicing Of Other Smn Exonsmentioning
confidence: 94%
“…[35][36][37] In addition, nutritional deficiency, oxidative stress, and hypoxia, partly attributed to gastrointestinal dysfunction, may cause widespread splicing alterations, including SMN2, and accelerate SMA progression. [38][39][40] How Low Levels of SMN Cause SMA Recent insights into the role of SMN within motor neurons have furthered our understanding of the implications of SMN deficiency. 41 The best characterized role of the SMN complex is in the assembly of Sm proteins (a distinctive family of RNA associated small proteins) onto small nuclear RNAs (snRNAs), forming small nuclear ribonucleoproteins (snRNPs), which are essential components of pre-mRNA splicing machinery in cells.…”
Section: Genetic and Environmental Insights Into Pathogenesismentioning
confidence: 99%
“…However, the consequences of low SMN levels on the synthesis of various selenoproteins in different tissues have not yet been assessed. Human SBP2 generates multiple alternatively spliced transcripts under normal and oxidative stress conditions [49,208,209]. Future studies will determine if various SBP2 isoforms interact with the SMN-TGS1 complex differently with the implications for the trafficking and/or translation of specific selenoprotein mRNAs.…”
Section: Role Of Smn In Rna Metabolismmentioning
confidence: 99%